Spatial Elements Imbued with Cognition: A possible step toward the "Architecture Machine". (December 2014) - Oungrinis, Konstantinos-Alketas; Liapi, Marianthi
When Nicolas Negroponte, in 1971, described future architecture as a 'machine', he was clear to ascribe this new character to intelligence and common sense rather than to kinesis and adaptation. Within this framework, the article presents a new direction toward the creation of an "Architecture Machine" which evolves from responsive architecture to include empathy control systems. The aim is set in two paths, with the first one exploring feasibility and the second securing unobtrusive operation to better facilitate human activity and comfort. The proposed architectural approach, for which the authors have coined the term sensponsive, employs Ambient Intelligence to imbue space with cognitive skills and provide it with a sense of why, how and when to act, while maintaining an empathic distance. Within this framework, the article presents a series of experiments to highlight the concepts and the techniques currently associated with a sensponsive design approach.